A textual analysis and an interpretation of towards a mystical reality / Loh Lean Choo - Loh, Lean Choo (2017)
Towards a Mystical Reality (TMR) was an event launched on 2nd August 1974, comprising an art exhibition, a debate and a written manifesto entitled, Towards a Mystical Reality: a documentation of jointly initiated experiences by redza piyadasa and sulaiman esa. This thesis concerns the criticism arising from local art intellectual discourse which views the manifesto as a problematic text and the definitions of Mystical Reality as unarticulated. This dissertation seeks to identify whether the criticisms from the art intellectuals are justifiable in response to the issues arising from the manifesto. The findings of this study posit that textually, the meaning of Mystical Reality is summed up in the last line of the manifesto text. The contextual meaning of Mystical Reality is found within the philosophical discourse partaken by Redza Piyadasa and Sulaiman Esa, which refers to the ‘mystical’ thinking of art, ‘mystical’ approach of reality and the initiated experiences that is ‘mental’, ‘mystical’ and ‘meditative’—this in sum, is the art of TMR (not the objects on display). The TMR manifesto text is remarkable for its attempt to articulate Zen experience and its methodological approach to advance art from Zen Reality. Despite the contradictions found through the textual analysis on the manifesto, TMR remained an art event which has sparked off a productive debate on art. Thus, it may be said that its contribution to local art discourse has so far been unrivalled.